Verimliliği etkileyen faktörlerden kalite ve kalite kontrolunun incelenmesi - Coşar, Şakir (My University, 1989)
﻿ ﻿ Özet In- this şurrej P productivity and the quality being ©ne of sain factors effecting productivity is Eany way® and the quality control has been covered,, Shiss survey has been handled in three different sections 9 la the first section, the information about productivity is included» la section, tis-o., the requirement fcr giving the overall infor mation about quality and the quality control has oe®n pointed out. fh® outcoae which aay and will be the result of the unguali- fled production has also been studied so as. to eaphasise the importance of quality and quality control* In section. three ? as the quality and quality control of foven faerie r gray cloth and fabric cloth in textile industry has been touched upon errors due technic in fabric has been explained and e^asipliyiedo (Photographs attached)
Keywords: Kalite; Kalite Kontrol